Mountain Path - Arnow, Harriette Louisa Simpson, 1908-1986 (Book collections on Project MUSE., 2012)
The book is not merely the tale of a few things that happened in the hill country. It is the story of conflicting ways of life, of a girl who, against her will, went to a backwoods community to teach and who, still against her will, learned more than she taught."